EMPLOYEES’ INTENTION TO USE A PERSONNEL MANAGEMENT INFORMATION SYSTEM: THE ROLES OF PERCEIVED USEFULNESS AND PERCEIVED EASE OF USE AT THE NATIONAL SEARCH AND RESCUE AGENCY - Yunita; Henry Eryanto; Umi Widyastuti (Faculty of Economics and Business, Universitas Negeri Jakarta, 2026)
This study aims to analyze the influence of perceived usefulness and perceived ease of use on the intention to use the personnel management information system at the National Search and Rescue Agency (BASARNAS). A quantitative approach was employed, utilizing a survey method involving 116 employees selected through a saturated sampling technique. Data were collected via questionnaires and analyzed using Partial Least Squares-Structural Equation Modeling (SEM-PLS). The results indicate that both perceived usefulness and perceived ease of use have a positive and significant effect on the intention to use, while perceived ease of use positively influences perceived usefulness. Furthermore, perceived usefulness was found to partially mediate the relationship between perceived ease of use and the intention to use. This study reinforces the application of the Technology Acceptance Model (TAM) within the public sector and offers practical utility for BASARNAS to optimize interface usability and system utility, thereby supporting administrative efficiency regarding personnel management.